'There is nothing nano-specific here': a reconstruction of the different understandings of responsiveness in responsible nanotechnology innovation. Issue 2 (4th May 2022) - Heltzel, Anouk; Schuijer, J. W.; Willems, W.L.; Kupper, F.; Broerse, J. E. W.
ABSTRACT: In the past decades, controversies in science and technology have fuelled the call for a research and innovation system that is open to public scrutiny and sensitive to public needs and values. These calls have been translated into a framework for responsible research and innovation (RRI). Despite its crucial role in RRI, the dimension of responsiveness is still considered to be the least conceptualized. In this paper, we analyse the mutual search for the meaning of `responsiveness' during a multi-stakeholder dialogue on responsiveness in nanotechnology innovation. We reconstructed five frames of responsiveness: science and technology, market, expert, network, and society-driven responsiveness. We highlighted and reflected on the three main strategies for dealing with differences: avoidance, polarization, and reframing. On the basis of our findings, we argue that in order to generate a collective meaning of responsiveness with a clear direction, conversations are needed in which fundamental assumptions can be questioned.